2009
DOI: 10.1016/j.clim.2008.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Can oligomeric T-cell receptor be used as a tool to detect viral peptide epitopes on infected cells?

Abstract: We have utilized soluble HIV Gag-specific T-cell receptor (TCR) D3 with low affinity and TCRlike antibody 25-D1.16 recognizing its natural peptide-MHC (pMHC) ligand with high affinity to determine how affinity and off-rate of the receptor-pMHC interactions affect the sensitivity of pMHC detection on the cell surface. We found that with soluble TCR cognate pMHCs can be detected only at relatively high cell surface densities when the TCR was oligomerized using either Strepavidin or quantum dots (QD) scaffolds. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The DHLA-capped QD-520 and QD-620 (emission wavelength 520 or 620 nm, respectively) were produced as previously described (Anikeeva et al, 2006; Anikeeva et al, 2009). For some experiments we utilized QDs encapsulated into lipid micelles (Evident Technology) as described elsewhere (Anikeeva et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DHLA-capped QD-520 and QD-620 (emission wavelength 520 or 620 nm, respectively) were produced as previously described (Anikeeva et al, 2006; Anikeeva et al, 2009). For some experiments we utilized QDs encapsulated into lipid micelles (Evident Technology) as described elsewhere (Anikeeva et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…For some experiments we utilized QDs encapsulated into lipid micelles (Evident Technology) as described elsewhere (Anikeeva et al, 2009). …”
Section: Methodsmentioning
confidence: 99%
“…Despite the high sensitivity of TCR multimers, no pMHC complexes were detectable by flow cytometry after staining hepatocytes transduced with AAV in culture (our unpublished observations). Others have shown that flow cytometry can limit the detection of low-density pMHC complexes by soluble TCR, as compared with more sensitive confocal imaging (16). We therefore investigated whether our TCR multimer could detect pMHC complexes by confocal microscopy.…”
Section: Figurementioning
confidence: 99%
“…The complexes formed by streptavidin with biotinylated MHC, usually called tetramers, vary in the number of biotinylated MHC molecules per streptavidin (SA) molecule (33, 34). Figure 1A shows the distribution of oligomers when biotinylated class I MHC and SA were combined at different molar ratios.…”
Section: Resultsmentioning
confidence: 99%